Big food and drink sponsorship of conferences and speakers: a case study of one multinational company's influence over knowledge dissemination and professional engagement - Jónas Atli Gunnarsson; Gary Ruskin; David Stuckler; Sarah Steele (Cambridge University Press, 2023)
Abstract Objectives: Research identifies that multinational corporations, including The Coca-Cola Company ('Coca-Cola'), seek to influence public health research and policy through scientific events, such as academic and professional conferences. This study aims to understand how different forms of funding and sponsorship impact the relationship between Coca-Cola, academic institutions, public health organisations, academics and researchers. Design: The study was conducted using Freedom of Information (FOI) requests and systematic website searches. Setting: Data were collected by twenty-two FOI requests to institutions in the USA and UK, resulting in the disclosure of 11 488 pages, including emails and attachments relating to 239 events between 2009 and 2018. We used the Wayback Machine to review historical website data to evaluate evidence from 151 available official conference websites. Participants: N/A Results: Documents suggest that Coca-Cola provides direct financial support to institutions and organisations hosting events in exchange for benefits, including influence over proceedings. Coca-Cola also provided direct financial support to speakers and researchers, sometimes conditional on media interviews. Also, indirect financial support passed through Coca-Cola-financed non-profits. Often, such financial support was not readily identifiable, and third-party involvement further concealed Coca-Cola funding. Conclusion: Coca-Cola exerts direct influence on academic institutions and organisations that convene major public health conferences and events. These events offer Coca-Cola a vehicle for its messaging and amplifying viewpoints favourable to Coca-Cola's interests. Such corporate-sponsored events should be viewed as instruments of industry marketing. Stronger rules and safeguards are needed to prevent hidden industry influence, such as complete disclosure of all corporate contributions for public health conferences and their speakers.